Ograniczenia dopuszczalności złożenia wniosku o przyznanie prawa pomocy przed sądem administracyjnym - Talaga, Robert (Studia Prawa Publicznego, 2020)
The right to a fair trial remains a common heritage of European legal culture. Such a standard has been guaranteed under the functioning system of human rights. Equally, the right to a fair trial was confirmed in the Constitution of the Republic of Poland. It does not mean unlimited access to justice without bearing the costs of the initiated proceedings. As a result, mechanisms were created to bear the costs of proceedings and to release certain categories of citizens from such an obligation. In proceedings before administrative courts, it is possible to apply for the right to assistance in order to maintain the right to judicial control of public administration activities. However, the relevant request from the person involved is subject to certain formal requirements. Among other things, it should be submitted using the appropriate official form, and the information contained therein may also indicate the manner in which the request was submitted. An application for granting the right to assistance may be submitted in the course of court proceedings or before their initiation. However, such a statutory definition of the moment for submitting an application for the right to assistance requires clarification. In fact, such a request cannot be made before the individual has been entitled to submit the appropriate appeal to the administrative court. Failure to comply with such a requirement results in the fact that the application submitted for the right to assistance does not generate any legal effects. A person applying for aid from the state is not yet obliged to bear court costs. There is also no need to provide such persons with professional legal assistance in proceedings before administrative authorities. This situation makes it impossible to grant the right to assistance due to the systemic limitations. In effect, such a procedure under the application for granting the right to assistance is discontinued as being deemed redundant. Moreover, premature submission of an application for the right to assistance may also reveal additionally that the substantive examination of the complaint or objection is inadmissible.